Traditional Indonesian food: A bibliometric review from 2013-2022 - Muspirah Djalal; Jamyang Tashi Wangdi; Andi Dirpan; Februadi Bastian; Rindam Latief; Andi Fadiah Ainani; Dewi Sisilia Yolanda (jurnal1, 2022)
Traditional food is a heritage of a country and therefore brings pride to a country or region. A bibliometric analysis of traditional Indonesian food was conducted in this paper to see the trend over the last decade, analyze the contribution of countries, and analyze the most frequently used keywords. A total of 102 documents were gathered from 66 different sources, including 57 articles, 36 conference papers, 4 reviews, 4 book chapters, and 1 data paper. According to this review, Indonesia is the most productive country in terms of producing articles (92) in this field, as well as having the most citations (315), despite having the lowest average number of citations per article. Surya R was the most productive author, with four documents, and Nuraida L had the most citations, with 111. Tempeh was also the most frequently used keyword, with 13 occurrences. It was hoped that this overview would help to advance research in traditional Indonesian food.